FRI0041 Improvements in functional status due to anakinra therapy in patients with rheumatoid arthritis who are not using dmards. (1st June 2001) - Emery, P; Woolley, JM; Chan, WW
Abstract : Background: Objectives: To evaluate the effect of anakinra on the functional status of subjects with rheumatoid arthritis who were not using DMARDs. Methods: In a 24-week, multicenter, randomised, double-blind clinical trial conducted in Europe, 473 subjects received either one of three doses of anakinra (30 mg, 75 mg, or 150 mg) or placebo SC QD. Subjects were excluded if they used DMARDs within six weeks of entry, or if they had failed therapy with more than three DMARDs. Functional status was measured by the HAQ, which was administered at baseline and at weeks 12 and 24. The mean change in HAQ score was compared between subjects receiving anakinra (all doses combined) and those on placebo. All subjects who completed at least one post-baseline assessment were included (n = 452) and the last-observation was carried forward in the case of missing data. Results: As shown in the Table 1, functional status improved for subjects on anakinra as their mean HAQ scores decreased by an average of 0.24. This improvement was both statistically significant, clinically important, and superior to the mean change in subjects receiving placebo. This result was true for each dose of anakinra, as compared to placebo (data not shown). Conclusion: Subjects receiving anakinra experienced statistically significant improvements in their HAQ scores that exceeded those for subjects on placebo. These improvements were of a magnitude considered clinically important. In subjects with rheumatoid arthritis who are not receiving DMARD therapy, anakinra leads to improvements in functional status.